Provocative Tests for Myocardial Ischemia in Patients with Implantable Electronic Cardiac Devices - Chiari Cabral, Gustavo; Lima Pinto, Gabrielle; Di Leoni Ferrari, Andres; Caroline Feltrin Willes, Jessica; Caramori, Paulo Ricardo Avancini (JOURNAL OF CARDIAC ARRHYTHMIAS, 2021)
Objective: Review the current literature in search of better knowledge about the use of implantable devices in patients who are investigating ischemic heart disease, and evaluate the possibility of its systematic use. Methods: Non-systematic literature review with exams and studies already published to date. Results: Risk stratification using implantable cardiac devices, associated with or as a substitute for the use of medication or physical stress, seems to be very safe, effective and highly reliable when compared to the methods traditionally established. Conclusion: Patients with implantable cardiac electronic devices constitute a specific challenging population, while research on ischemia is limited by secondary low/bay perfusion changes that result from the interaction of the device with the heart. These changes must be previously known, expected and interpreted with great care in order to reduce the number of false positives.